Harmonisasi Norma Adat dan Syariat Islam Terhadap Tradisi Kawin Boyong di Desa Sembung Kecamatan Parengan Kabupaten Tuban - Fina Mawahib (Jayapangus Press, 2026)
Kawin Boyong (marriage) is a traditional custom still preserved by the people of Sembung Village, Parengan District, Tuban Regency, where the prospective husband temporarily resides at the prospective wife's house before the marriage ceremony. This tradition arises from the belief in Javanese weton calculations, which are the basis for determining the suitability of the wedding day. However, when examined from an Islamic legal perspective, the nikah boyong tradition contains elements of khalwat (being alone between a man and a woman who are not mahram). In Islam, khalwat is forbidden because it can potentially lead to sin and acts close to adultery. The purpose of this study was to analyze the practice of the nikah boyong tradition in Sembung Village based on customary law and Islamic law. The study was conducted using a qualitative approach through observation, interviews, and comparative analysis. Primary data were obtained from four informants, namely traditional leaders, religious leaders, and the prospective bride and groom, and were supported by secondary data in the form of relevant book and journal articles. Then, the data were analyzed using thematic analysis and data validation techniques were carried out using member checking. The research found that, from a customary law perspective, the nikah boyong tradition is viewed as a means to prevent future marriage mates from misfortune or disaster. Meanwhile, Islamic law considers the practice of nikah boyong to have the potential to lead to khalwat (independent interaction) that could lead to adultery. Therefore, nikah boyong should ideally be carried out in a limited, monitored manner, and in accordance with religious norms to maintain the sanctity of marriage and family honor. Therefore, this tradition can be modified by shortening the length of stay, collaborating with traditional, religious, and family leaders, or replacing physical presence with symbolic ones to maintain cultural value without violating religious norms.